Use of Value-at-Risk for the Quantification of Risks in Insurance - Zahra, EL ARIF Fatima (Review of Knowledge Economy, 2014)
Value-at-Risk has become a standard for managing risk in the financial world. The purpose of this article is to specify the conditions under which the VaR could be a good measure of risk asset in insurance. After the description of the main approaches to calculating VaR currently employed in the insurance industry, we will indicate the specific financial management in insurance. We then present the necessary changes in VaR and its limitations, and alternatives to VaR for risk calculation (Method of generalized scenarios, CVaR).